A efetividade da sanção jurídica por ausência de licenciamento ambiental de estações de rádio base nas decisões judiciais diante do princípio da precaução - Faistel, Franciele (2019)
The growth of Radio Base Stations (BRBs) in Brazil, due to the increase in the number of cell phones, became a concern due to the risks to human health, when evidenced the absence of environmental licensing. The installation of radio base antennas in urban areas grows uncontrolled in the country. However, UN health agencies and some countries warn of the problem of radiation emissions (between 9 KHz and 300 GHz), which has become a type of non-visible pollution, such as electromagnetic radiation from antennas, which, from the point of view of sustainable development, is a negative economic externality. The growth of ERBs without environmental licensing, however, concerns physical researchers, engineers, biologists and medicine, who have found evidence of the relationship between radiation from BERs and risks to human health. One of the instruments adopted in several countries in the world, including Brazil, which effectively controls activities and ventures that potentially cause environmental impacts, is Environmental Licensing. This study focuses on the process of absence of environmental licensing of Base Radio Antennas (BRA / ERBs), since it intends to monitor, control and control these activities of the licensing act itself. However, more detailed studies on the effectiveness of the legal / sanction rule on the absence of licensing of BERs have become necessary in view of the precautionary principle. The objective of this research is to analyze the effectiveness of the application of legal sanction in judicial decisions theorized in the precautionary principle, highlighting the absence of environmental licensing of ERBs between the years 2010-2018 in 6 states of the country (SE , RS, PR, DF, MG and SP). The methodology chosen to answer the proposed objectives was the theoretical documentary research, based on judicial processes available on the websites of the Courts of Justice of Sergipe, Rio Grande do Sul, Paraná, Federal District and Territories, Minas Gerais and São Paulo, proceeding to the documents the Superior Court of Justice and the Federal Supreme Court. In the analysis of the jurisprudence of the Courts of Justice of the country, it was sought to verify the effectiveness of the sanction imposed by the public entity or by the judiciary, in view of the precautionary principle in cases where there was no environmental licensing of Base Radio Antennas, study of the law and its application in the decisions of concrete cases. Through the analysis, it is concluded that the effectiveness of the legal sanction does not occur in many cases due to recurrent legislative changes, the way in which the sanction is applied and the civil process itself that allows the lodging of numerous judicial remedies. In this way, it is pointed out that as long as the precautionary principle does not take effect in the legal norm itself, the sanction ends without effectiveness.